2007
DOI: 10.1103/physrevb.75.155325
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of quantum dots on off-normal incidence ion sputtered surfaces

Abstract: We implement substrate rotation in a 2 + 1-dimensional solid-on-solid model of ion-beam sputtering of solid surfaces. With this extension of the model, we study the effect of concurrent rotation, as the surface is sputtered, on possible topographic regions of surface patterns. In particular, we perform a detailed numerical analysis of the time evolution of dots obtained from our Monte Carlo simulations at off-normal-incidence sputter erosion. We found the same power-law scaling exponents of the dot characteris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…They found that without rotation, the average number of dots decreases with increasing fluence, while it remains nearly constant for a rotating sample. In addition, the uniformity of dots enhances by sample rotation [26]. Similar is the case for us in InP where we observe the reduced number of dots for increasing ion fluence.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…They found that without rotation, the average number of dots decreases with increasing fluence, while it remains nearly constant for a rotating sample. In addition, the uniformity of dots enhances by sample rotation [26]. Similar is the case for us in InP where we observe the reduced number of dots for increasing ion fluence.…”
Section: Resultssupporting
confidence: 71%
“…Indeed, this is the case for the present study where the Ar-ion penetration depth varies from 84 to 72.7 to 42 nm corresponding to normal-and obliqueincidences of 308 and 608, respectively. Later on, they studied the time evolution of dots originating from oblique ion incidence by performing Monte Carlo simulations for GaAs and Si [26]. They found that without rotation, the average number of dots decreases with increasing fluence, while it remains nearly constant for a rotating sample.…”
Section: Resultsmentioning
confidence: 97%
“…This assumption corresponds to the limit of high rotation frequencies. Dots also appear in MC simulations performed in the high rotation frequency limit for a wide range of parameters [16].…”
Section: Sputtering Of Continuously Rotating Samplementioning
confidence: 91%
“…Our simulation method has been described several times, more details can be found in Refs. [8,9,10,11]. We use a lattice gas, solid-on-solid model.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%